Triiodothyronine regulates angiogenic growth factor and cytokine secretion by isolated human decidual cells in a cell-type specific and gestational age-dependent manner - Vasilopoulou, E.; Loubière, L.S.; Lash, G.E.; Ohizua, O.; McCabe, C.J.; Franklyn, J.A.; Kilby, M.D.; Chan, S.Y. (Human reproduction (Oxford), 2014)
STUDY QUESTION Does triiodothyronine (T3) regulate the secretion of angiogenic growth factors and cytokines by human decidual cells isolated from early pregnancy? SUMMARY ANSWER T3 modulates the secretion of specific angiogenic growth factors and cytokines, with different regulatory patterns observed amongst various isolated subpopulations of human decidual cells and with a distinct change between the first and second trimesters of pregnancy. WHAT IS KNOWN ALREADY Maternal thyroid dysfunction during early pregnancy is associated with complications of malplacentation including miscarriage and pre-eclampsia. T3 regulates the proliferation and apoptosis of fetal-derived trophoblasts, as well as promotes the invasive capability of extravillous trophoblasts (EVT). We hypothesize that T3 may also have a direct impact on human maternal-derived decidual cells, which are known to exert paracrine regulation upon trophoblast behaviour and vascular development at the uteroplacental interface. STUDY DESIGN, SIZE, DURATION This laboratory-based study used human decidua from first (8–11 weeks; n = 18) and second (12–16 weeks; n = 12) trimester surgical terminations of apparently uncomplicated pregnancies. PARTICIPANTS/MATERIALS, SETTING, METHODS Primary cultures of total decidual cells, and immunomagnetic bead-isolated populations of stromal-enriched (CD10+) and stromal-depleted (CD10−) cells, uterine natural killer cells (uNK cells; CD56+) and macrophages (CD14+) were assessed for thyroid hormone receptors and transporters by immunocytochemistry. Each cell population was treated with T3 (0, 1, 10, 100 nM) and assessments were made of cell viability (MTT assay) and angiogenic growth factor and cytokine secretion (immunomediated assay). The effect of decidual cell-conditioned media on EVT invasion through Matrigel® was evaluated. MAIN RESULTS AND THE ROLE OF CHANCE Immunocytochemistry showed the expression of thyroid hormone transporters (MCT8, MCT10) and receptors (TRα1, TRβ1) required for thyroid hormone-responsiveness in uNK cells and macrophages from the first trimester. The viability of total decidual cells and the different cell isolates were unaffected by T3 so changes in cell numbers could not account for any observed effects. In the first trimester, T3 decreased VEGF-A secretion by total decidual cells (P < 0.05) and increased angiopoietin-2 secretion by stromal-depleted cells (P < 0.05) but in the second trimester total decidual cells showed only increased angiogenin secretion (P < 0.05). In the first trimester, T3 reduced IL-10 secretion by total decidual cells (P < 0.05), and reduced granulocyte macrophage colony stimulating factor (P < 0.01), IL-8 (P < 0.05), IL-10 (P < 0.01), IL-1β (P < 0.05) and monocyte chemotactic protein -1 (P < 0.001) secretion by macrophages, but increased tumour necrosis factor-α secretion by stromal-depleted cells (P < 0.05) and increased IL-6 by uNK cells (P < 0.05). In contrast, in the second trimester T3 increased IL-10 secretion by total decidual cells (P < 0.01) but did not affect cytokine secretion by uNK cells and macrophages. Conditioned media from first trimester T3-treated total decidual cells and macrophages did not alter EVT invasion compared with untreated controls. Thus, treatment of decidual cells with T3 resulted in changes in both angiogenic growth factor and cytokine secretion in a cell type-specific and gestational age-dependent manner, with first trimester decidual macrophages being the most responsive to T3 treatment, but these changes in decidual cell secretome did not affect EVT invasion in vitro. LIMITATIONS, REASONS FOR CAUTION Our results are based on in vitro findings and we cannot be certain if a similar response occurs in human pregnancy in vivo. WIDER IMPLICATIONS OF THE FINDINGS Optimal maternal thyroid hormone concentrations could play a critical role in maintaining a balanced inflammatory response in early pregnancy to prevent fetal immune rejection and promote normal placental development through the regulation of the secretion of critical cytokines and angiogenic growth factors by human decidual cells. Our data suggest that there is an ontogenically determined regulatory ‘switch’ in T3 responsiveness between the first and second trimesters, and support the notion that the timely and early correction of maternal thyroid dysfunction is critical in influencing pregnancy outcomes. STUDY FUNDING/COMPETING INTEREST(S) This study is funded by Wellbeing of Women (RG/1082/09 to S.Y.C., M.D.K., J.A.F., L.S.L., G.E.L.) and Action Medical Research – Henry Smith Charity (SP4335 to M.D.K., S.Y.C., L.S.L., J.A.F.). The authors have no conflicts of interest to disclose.